Optimizing Surakarta (Solo) as a Tourism City Brand to Enhance Community Economic Welfare: An Islamic Economic Perspective - Muhammad Pradipta Handika Putra; Muthoifin (Demak Universal Journal of Islam and Sharia, 2025)
Objective: This study aims to analyze the potential of optimizing Surakarta (Solo) as a tourism city icon to enhance community economic welfare from an Islamic economic perspective. Solo is widely recognized for its rich cultural heritage, historical attractions, and Islamic religious destinations, making it a strategic city for the development of sustainable and Sharia-compliant tourism. Theoretical framework: The theoretical framework of this study is grounded in Islamic economics, particularly the concept of mu’amalah, which emphasizes economic activities that promote social welfare, ethical values, and compliance with Islamic principles. Tourism is viewed not only as an economic sector but also as a means of achieving maslahah (public benefit) for society. Literature review: The literature review highlights previous studies on tourism development, regional economic growth, religious tourism, and Sharia tourism, indicating that tourism significantly contributes to employment creation, local income generation, and community empowerment. However, limited studies have specifically examined the optimization of Solo’s tourism potential through the lens of Islamic economics. Method: This research employs a literature review method by analyzing relevant academic publications, government reports, and tourism-related documents. Results: The findings reveal that tourism indicators, including the number of tourist arrivals, average length of stay, hotel occupancy rates, and accommodation availability, play a significant role in supporting regional economic development. Furthermore, Islamic tourism in Solo, such as the Sheikh Zayed Grand Mosque, the tombs of Kyai Ageng Henis and Ki Gede Sala, and Langgar Merdeka, possesses substantial potential to attract domestic and international visitors. From a Sharia perspective, tourism activities should adhere to Islamic values, ensuring ethical business practices and social benefits. Implications: The study implies that policymakers, tourism stakeholders, and local communities should strengthen the promotion, infrastructure, and management of Sharia-based tourism destinations to maximize their economic impact. Novelty: The novelty of this study lies in integrating tourism optimization strategies with Islamic economic principles to enhance community welfare and strengthen Solo’s identity as a leading Islamic tourism destination.